Behavior and Needs in using the Public Transportation of Japanese Tourists - เกิดฤทธิ์ กนิฏฐา (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The objectives of the research were as following; 1) to study the behavior and the needs of service use the Public Transportation of Japanese tourists, 2) to compare the behavior and requirements of service use the Public Transportation of tourists from Japan by classified according to personal factor, 3) to study the needs of the service using the public bus service of Japanese tourists and 4) to compare the needs and requirements of service use the Public Transportation of tourists from Japan by classified according to personal factors. The samples were 400 Japanese Tourists. Collected was by questionnaire. Data was analyzed by frequency, percentage, mean, standard deviation, difference test by t-test and One-way ANOVA. From the study the behavior of Japanese tourists who used public transportation service was as follows: Japanese tourists use the service BTS/MRT/ARL most. The Japanese tourists to use services most is the time 09.31 pm. - 15.30 pm. more than 4 times per week with their family. A comparison between the behavior of the public transportation. Male and female of Japanese tourist have difference behavior when use public transportation service. Japanese tourists with different occupation and education have different behavior in using public transportation service. The need to use the public transportation of Japanese tourists. Overall, the needed at high level. The quality and safety of the service in public transport. As the traveler is the most demanding. Comparison between the demand for public transportation services of Japanese tourists with occupation found that the overall needs of each side were different.